Assessing the Reproductive Health Knowledge of Early Adolescents in North Coastal Line - ., Juariah (KnE Life Sciences, 2019)
Adolescents residing in the North Coastal line have high risks associated with reproductive health. The is due to the entertainment industry and prostitution business in the area creating an unfavorable environment for adolescents. A young mating culture is also strong. The high rate of divorce and the number of mothers who become Indonesian women laborers working abroad weakens the role of parents in character building and the moral education of adolescents. It allows adolescents to fall into sexual activity, drug use, and HIV infection. The purposes of this study were to gain insight into adolescents in the North Coastal line and their families and to assess the baseline reproductive health knowledge of the adolescents. Thus, the interventions suggested based on their needs. A cross-sectional study was conducted in Pusakajaya Public Junior High School 1 and 2, in which 269 seventh grade students (male=135, female=134) were interviewed using a semi-structured questionnaire. Respondents were chosen using purposive sampling. Data analyzed with univariate analysis. Results of this study showed that most of the adolescents confessed to being less than obedient to their religion. More than half of them were not actively engaged in school and were poorly motivated to do well. Many of them lived with a single parent or relatives. Many parents of the adolescents were divorced, most had a low level of education, some were unemployment, and many of the mothers worked as Indonesia women laborers abroad. The findings of this study showed that all aspects of reproductive health knowledge of the adolescents that include female puberty signs, male puberty signs, adolescent pregnancy risk, HIV/AIDS, sexually transmitted diseases and risk of smoking and substance abuse were in the ‘poor’ category (90.3%, 99.6%, 100%, 89.2%, 98.1% and 99.3% respectively). Keywords: reproductive health, knowledge, early adolescent, north coastal line